Human Dignity and Rights of Persons with Disabilities - Atienza Rodríguez, Manuel (2016)
In this article, the author analyzes the impact of the Kantian concept of human dignity in the UN Convention on the Rights of Persons with Disabilities. Likewise, the author elaborates a critique of the principle which argues that persons with disabilities’ individual autonomy and capacity to make decisions must be respected, regardless of the particular circumstances of the case, and finally proposes an interpretation of this principle based on the principle of equality.